2016
DOI: 10.1073/pnas.1616710113
|View full text |Cite
|
Sign up to set email alerts
|

Singular role for T-BET + CXCR3 + regulatory T cells in protection from autoimmune diabetes

Abstract: Foxp3+ regulatory T (Treg) cells are crucial for restraining inflammation in a variety of autoimmune diseases, including type 1 diabetes (T1D). However, the transcriptional and functional phenotypes of Treg cells within the pancreatic lesion remain poorly understood. Here we characterized pancreas-infiltrating Treg cells in the NOD mouse model of T1D and uncovered a substantial enrichment of the Treg subpopulation expressing the chemokine receptor CXCR3. Accumulation of CXCR3 + Treg cells within pancreatic isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 53 publications
7
86
0
1
Order By: Relevance
“…Several groups have described cotranscription factor expression by Tregs as being necessary for their ability to suppress specific T helper lineages (32,(44)(45)(46)(47). Explicitly, coexpression of Foxp3 and T-bet by Tregs is indispensable for their ability to prevent autoimmune diabetes (32). In line with this idea, RNA-seq analysis revealed that functionally superior CD5 hi islet Tregs exhibited an enhanced T-bet program ( Figure 3F).…”
Section: Tcr Affinity Drives T-bet Expression In Tregsmentioning
confidence: 62%
See 4 more Smart Citations
“…Several groups have described cotranscription factor expression by Tregs as being necessary for their ability to suppress specific T helper lineages (32,(44)(45)(46)(47). Explicitly, coexpression of Foxp3 and T-bet by Tregs is indispensable for their ability to prevent autoimmune diabetes (32). In line with this idea, RNA-seq analysis revealed that functionally superior CD5 hi islet Tregs exhibited an enhanced T-bet program ( Figure 3F).…”
Section: Tcr Affinity Drives T-bet Expression In Tregsmentioning
confidence: 62%
“…ICOS has previously been shown to identify a highly functional islet-infiltrating Treg population, which preferentially upregulates CXCR3, suggesting an important role for TCR in driving the program necessary for regulation of Th1 islet autoimmunity (32,52,53).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations